DAMPAK PARIWISATA TERHADAP KONDISI SOSIAL BUDAYA MASYARAKAT DI BANDA ACEH - Swesti, Woro (Jurnal Kepariwisataan Indonesia : Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Various conditions are force the tourism development in Banda Aceh, one of them is tsunami wave in 2006. The condition of the people of Aceh who had been in a bad political and security with the presence of military operations and prolonged conflict, affected the way the Aceh community interacts with migrant (tourists). The study of the impact of tourism on socio-cultural is important to ensure that tourism development in Aceh does not disturb the sustainability of the socio-cultural aspects. The interaction between tourists and local people in Banda Aceh has a social and cultural impact. The socio-cultural impact of tourism development can be seen from the preservation of local culture such as traditional dances, Aceh's cultural history, preservation of various historic buildings in Aceh. While the negative impact of tourism on socio-cultural conditions can be seen from the response of local communities to the existence of tourism such as the emergence of conflicts of interest among stakeholders, and social problems such as gambling and prostitution. Some of part of the communities who think that tourism development is against Islamic law is become a challenge for tourism policy makers in Aceh. To anticipate this, it is necessary to change the strategy in developing tourism in Aceh. The community needs to be involved in determining policies and decisions related to tourism in their area.